Denial and Skepticism in Al-Ghazali’s Theory of Knowledge - Andi Nurbaethy (JICSA : Journal of Islamic Civilization in Southeast Asian, 2015)
This paper presents an elaboration on Al-Ghazali’s intellectual and spiritual struggle in searching for certitude to establish secure basis for his theory of knowledge. The elaboration starts with introducing Al-Ghazali’s definition and classification of knowledge, discussing the important of both sacred and profane knowledge as he categorizes of them into personal and collective obligations, and develop into presenting his schema of knowledge. Further discussion then focuses on essential staging in his intellectual and spiritual inquiry to reach the final stage of a personal testimony of doubtless true knowledge. Initiated with a total denial of knowledge to abolish uncertainty to its fullest extent, his struggle then proceeded to the level of extreme skepticism proceeding establishment of his fundamental theory of knowledge.